2021
DOI: 10.15252/emmm.202013591
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological or genetic inhibition of iNOS prevents cachexia‐mediated muscle wasting and its associated metabolism defects

Abstract: Cachexia syndrome develops in patients with diseases such as cancer and sepsis and is characterized by progressive muscle wasting. While iNOS is one of the main effectors of cachexia, its mechanism of action and whether it could be targeted for therapy remains unexplored. Here, we show that iNOS knockout mice and mice treated with the clinically tested iNOS inhibitor GW274150 are protected against muscle wasting in models of both septic and cancer cachexia. We demonstrate that iNOS triggers muscle wasting by d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 126 publications
1
7
0
Order By: Relevance
“…jp/), The Kyoto Encyclopedia of Genes and Genomes (KEGG; https://www.genome.jp/kegg/), and software such as MetaboAnalyst 5.0 (https://www.metaboanalyst.ca/) (Pang et al, 2021). A growing number of studies have been using MetaboAnalyst website to conduct the pathway analysis and ROC analysis in CC studies (Yang et al, 2018;Cui et al, 2019b;Sadek et al, 2021).…”
Section: Data Elucidationmentioning
confidence: 99%
See 1 more Smart Citation
“…jp/), The Kyoto Encyclopedia of Genes and Genomes (KEGG; https://www.genome.jp/kegg/), and software such as MetaboAnalyst 5.0 (https://www.metaboanalyst.ca/) (Pang et al, 2021). A growing number of studies have been using MetaboAnalyst website to conduct the pathway analysis and ROC analysis in CC studies (Yang et al, 2018;Cui et al, 2019b;Sadek et al, 2021).…”
Section: Data Elucidationmentioning
confidence: 99%
“…Increased expressions of inducible nitric oxide synthase (iNOS) have been observed in muscle tissues of cancer, AIDS, chronic heart failure, and COPD cachexia patients, suggesting that iNOS may be involved in the onset of cachexia under various conditions (Adams et al, 2003;Agusti et al, 2004;Ramamoorthy et al, 2009). Sadek and colleagues identified a signature of amino acids that were altered by iNOS activity in muscle by performing LC-MS-based and GC-MS-based metabolomic analyses based on the C26 murine model (Sadek et al, 2021). Notably, iNOS could significantly increase levels of arginine, lysine, tryptophan and methylhistidine, which could be decreased by inhibiting iNOS.…”
Section: Therapeutic Strategies By Using Metabolomicsmentioning
confidence: 99%
“…The treatment of muscle regeneration after an extensive injury has always been difficult. Many studies have shown a close link between muscle regeneration and immunity 30,31 . Those studies suggested that the regeneration process is traditionally divided into two parts: proinflammatory and anti‐inflammatory restorative phases, and the regeneration can be regulated by controlling the shift of the two phases 6 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the pharmacological inhibition of NF‐κB has proven its efficiency in cancer cachectic animals 27 . Besides, selective pharmacological inhibition of iNOS, which is a downstream effector of NF‐κB pathway and is highly expressed in cachectic muscle, 120 ameliorates cancer cachexia in mouse 120 …”
Section: Therapeutic Perspectivesmentioning
confidence: 99%
“…27 Besides, selective pharmacological inhibition of iNOS, which is a downstream effector of NF-κB pathway and is highly expressed in cachectic muscle, 120 ameliorates cancer cachexia in mouse. 120…”
Section: Tnfα-nf-κbmentioning
confidence: 99%